The Effects of Collaboration and Competition on Players’ Perceptions in Human Computation Games - Pe-Than, Ei Pa Pa (2016)
Human Computation Games (HCGs) harness human intelligence through games to address computational problems. Collaboration and competition have emerged as the most commonly used HCG genres. Yet, little research has examined the effects of such genres on players’ perceptions. Through an experimental study with 95 participants, this study investigates the effects of collaboration and competition on perceived enjoyment and output quality in mobile content sharing HCGs. The findings suggest that competition yielded better perception of output accuracy than collaboration. However, players derived more behavioral enjoyment from collaboration than competition in HCGs. The implications of these findings are discussed.